Power Sources for Remote Arctic Applications - United States. Congress. Office of Technology Assessment. (United States. Congress. Office of Technology Assessment., 1994)
This background paper concludes that continued use of the radioisotope thermoelectric generators (RTGs) at Burnt Mountain entails low risk for the safety of maintenance workers and local populations and for the environment.